Lithocarpus eiadthongii (Fagaceae), a new stone oak species from southern part of Thailand - Sinbumroong, Aroon; Rueangruea, Sukid; Teerawatananon, Atchara; Sungkaew, Sarawood (Phytotaxa, 2022)
A new species of the genus Lithocarpus, L. eiadthongii, from southern part of Thailand is described and illustrated. Its colour photographs are also provided and its conservation status is assessed. The new species is superficially similar to L. melataiensis, L. pusillus and L. vuquangensis in terms of leaf and fruit size. Notwithstanding, it differs from the three species in several aspects e.g. leaf apex, leaf blade covering, cupule stalk, cupule size, nut size and nut enclosure.